Suitability of Surface Water for Drinking purposes in Basrah City Using Water Quality Index (WQI) - Alak Hassan, Ayman (Iraqi Journal of Civil Engineering, 2018)
The water quality index (WQI) is applying for the integrating the water quality variables into a single number to indicate the overall quality of water. Rivers is one of the essential water resources, the protecting and preserving for the quality of this resource is important and imperative. An evaluation of water characteristics of the Shatt Al Arab River in Basrah city was performed in order to determine the quality of water for drinking usage. In this research, monitoring of variation in the characteristics of water was accomplished by collecting monthly water samples for three years. The water samples from the Shatt Al Arab River is analyzed for eight Physical and chemical parameters such as pH, total dissolved solids (TDS), electrical conductivity (EC), total hardness (TH), calcium (Ca), magnesium (Mg), sulphate (SO4) and chloride (Cl) using standard methods. Utilizing the WQI discovered that the water quality of the studied river is ranked between very poor water type and not suitable water for drinking usage category. In the present investigation, the quality of water was revealed that the average of WQI value for the studied years was 318, 337.3 and 456.7, respectively.